Hypothenar pressure mapping provides insight for reducing ulnar nerve compression in cyclists - Slane, J.; Timmerman, M.; Ploeg, H.; Thelen, D. (ESM 2010 emed scientific meeting, 2010)
Chronic ulnar nerve compression is believed to be a primary cause of sensory and motor impairments of the hand, which is common among cyclists. Prevention techniques include frequently changing hand position and wearing padded gloves. However to date, there has been no scientific examination into the effectiveness of these measures (Kennedy, 2008). The purpose of this study was to evaluate the effects of hand position and glove padding on pressure over the ulnar nerve. Specifically, we considered three hand positions commonly used on road bicycles. We also compared gloves with either 3 mm or 5 mm gel or foam padding placed over the hypothenar eminence, thenar eminence and metacarpal heads